Agenda for a critical decade: strategic plan 1993-2002 - CATIE - Centro Agronómico Tropical de Investigación y Enseñanza (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Throughout history, agriculture has been essential for human well-being and survival. Nevertheless, it has become one of the production sectors that most affect the environment and natural resources. Population growth resulted in a constantly increasing demand for food, which together with inappropriate use of natural resources, implementación of environmentally harmful production technologies, and lack of alternative employment in rural areas, has intensified the conflict between agricultural production and environmental conservation. This strategic plan, with its emphasis on strategic research, education and outreach strives to lay the foundations for helping society satisfy its food needs without damaging the environment and natural resources, thus improving that society’s standard of living.